Analysis of the volumetric relationship among human ocular, orbital and fronto‐occipital cortical morphology. Issue 4 (7th August 2015) - Masters, Michael; Bruner, Emiliano; Queer, Sarah; Traynor, Sarah; Senjem, Jess
Abstract Recent research on the visual system has focused on investigating the relationship among eye (ocular), orbital, and visual cortical anatomy in humans. This issue is relevant in evolutionary and medical fields. In terms of evolution, only in modern humans and Neandertals are the orbits positioned beneath the frontal lobes, with consequent structural constraints. In terms of medicine, such constraints can be associated with minor deformation of the eye, vision defects, and patterns of integration among these features, and in association with the frontal lobes, are important to consider in reconstructive surgery. Further study is therefore necessary to establish how these variables are related, and to what extent ocular size is associated with orbital and cerebral cortical volumes. Relationships among these anatomical components were investigated using magnetic resonance images from a large sample of 83 individuals, which also included each subject's body height, age, sex, and uncorrected visual acuity score. Occipital and frontal gyri volumes were calculated using two different cortical parcellation tools in order to provide a better understanding of how the eye and orbit vary in relation to visual cortical gyri, and frontal cortical gyri which are not directly related to visual processing. Results indicated that ocular and orbital volumes were weakly correlated, and that eye volume explains only a small proportion of the variance in orbital volume. Ocular and orbital volumes were also found to be equally and, in most cases, more highly correlated with five frontal lobe gyri than with occipital lobe gyri associated with V1, V2, and V3 of the visual cortex. Additionally, after accounting for age and sex variation, the relationship between ocular and total visual cortical volume was no longer statistically significant, but remained significantly related to total frontal lobe volume. The relationship between orbital and visual cortical volumes remained significant for a number of occipital lobe gyri even after accounting for these cofactors, but was again found to be more highly correlated with the frontal cortex than with the occipital cortex. These results indicate that eye volume explains only a small amount of variation in orbital and visual cortical volume, and that the eye and orbit are generally more structurally associated with the frontal lobes than they are functionally associated with the visual cortex of the occipital lobes. Results also demonstrate that these components of the visual system are highly complex and influenced by a multitude of factors in humans.